PENGARUH PEMBERIAN DOLOMIT TERHADAP KUALITAS DAN MASA SIMPAN BUAH SALAK GULA PASIR (Salacca zalacca (var.) Amboinensis) - Paulina Firsan; I Ketut Sumantra; Ni Putu Pandawani (Agrofarm: Jurnal Agroteknologi, 2022)
The study entitled "The Effect of Dolomite Doses on the Quality and Storage Period of Salak Salak Pasir" has been carried out from April 2019 to January 2020, from the time of dolomite administration to harvest. The study was carried out in farmers' salak gardens in Pajahan Village, Pupuan District, Tabanan Regency and the Agrotechnology Laboratory, Mahasaraswati University, Denpasar. The study was conducted in the field and laboratory using a Randomized Block Design (RBD) with 5 dolomite dosage treatments and 6 replications, so that there were 30 snake fruit plants used in this study. The dosage of dolomite that is applied and is a treatment consists of 5 levels, namely: D0 (0 kg dolomite per tree); D1 (1, 50 kg dolomite per tree); D2 (3 kg dolomite per tree); D3 (4, 50 kg of dolomite per tree) and D4 (6 kg of dolomite per tree). The effect of giving a number of dolomite doses on zalacca plants on the quality and shelf life of zalacca was observed from several parameters namely the parameters of fruit weight, fruit meat weight, seed weight, number of fruit skin scales, fruit flesh thickness and fruit shelf life. Statistical analysis results of the effect of dolomite administration on several parameters observed showed significantly different in the weight of the fruit seeds and very significantly different in the parameters of fruit weight, fruit weight, thick fruit flesh and shelf life of salak fruit. As it is known that dolomite in addition to containing Ca also contains Mg, which has a better effect on soils that have low Mg levels especially for fruit growth and yields From the results of this study it can be concluded that the quality of salak sugar in 1.5 kg dolomite dose significantly higher than the 6 kg dolomite dose; 4.5 kg; 3 kg, and 0 kg dolomite per tree indicated in the fruit meat weight parameters reached 35.06 grams and fruit meat thickness reached 1.02 cm. Giving several doses of dolomite in salak plants are 1.5 kg dolomite doses; 3 kg; 4.5 kg; and 6 kg per tree gives a shelf life of salak sugar which is not significantly different. The shelf life of zalacca sugar is significantly higher than that without dolomite when it occurs in dolomite doses of 1.5 kg per tree which is 13, 50 days. From the conclusion of this study it can be suggested that to improve the quality and shelf life of salak fruit, it is recommended that in salak cultivation be given dolomite 1, 5 kg per tree.